Revisions of National Accounts - Anne Sofie Jore (Norges Bank, 2017)
I investigate revisions of growth rates in nominal and real quarterly GDP for mainland Norway, as well as for the GDP deflator, from 2004 to 2016. Several measures from alternative revision periods are computed. Mean revisions of real GDP are small and close to zero, while nominal GDP and the deflator are under-predicted on average when they are first published. For all three variables, mean absolute revisions are quite substantial. Revisions can, in general, be explained by the arrival of new information, although revisions of the deflator in particular are also characterized as reducing noise.
hdl:11250/2506375
Keywords: 330